Identifying and surveying on Enterprise Architecture Issues and challenges in Iranian selected enterprises: Mixed method - Samira Parsa; Nastaran Hajiheydari; ebrahim abasi (Journal of Information Technology Management)
The purpose of this study is to identify issues on Enterprise Architecture through surveying subjectivity and opinions of participants. Exploration mixed research method was conducted which is based on qualitative meta-synthesis method and Q-methodology. In the first step, selecting studies were conducted to identify the most important issues that influence the success of Enterprise Architecture, a literature study of 21 articles and studies was conducted from different data bases. In the second step, synthesizing translations, we first assembled all the studies together and determined how they are related to each other. We then translated the studies with each other based on a comparative approach. In the last step, expressing the synthesis, we presented our new metaphor and consequently 14 issues are identified. Next, we used Q-methodology; it has been applied as a mixed method in this study. In this step we had 4 interviews with managers and experts to identify some more issues. Then we elicited the statements. Given the appraisal and summarization of concourse, a variety of concourse were discovered and obtained from various sources, and then 110 short statements were selected as Q-phrases. After a survey of experts, 43 Q-sample were chosen. , then we choose 21 participants which constitute managers and specialists on Enterprise Architecture to sort the Q-tests. After Q-sorting, the information was analyzed using factor analysis. Distribution analysis showed that 6 distinct subjective perspectives about the issues on Enterprise Architecture can be identified among participants which explained (70.770) percent of total variance. These 6 subjective perspectives were called as: "Managerialists", "Proficient control takers", "Complex minded", "Collaborative architects", "Analysts", and finally "Accurate architects". The importance and prioritization of issues were identified based on subjective perspectives.